2006
DOI: 10.1111/j.1365-2788.2006.00844.x
|View full text |Cite
|
Sign up to set email alerts
|

A review of the reliability and validity of Likert‐type scales for people with intellectual disability

Abstract: Likert-type scales should include pictorial representations of response alternatives, a single set of one or two word response descriptors, clarifying questions, and pretests, and are best used with adolescents and adults with borderline IQ to mild ID.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
222
0
10

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(238 citation statements)
references
References 70 publications
6
222
0
10
Order By: Relevance
“…This procedure has been shown to successfully elicit coping responses among adults with mild ID (Hartley & MacLean, 2005;Lunsky, 2003;Wayment & Zetlin, 1989). A sentence stem task has the advantage of avoiding the endorsement of socially desirable responses and other response biases associated with yes-no, either-or and Likert scale questionnaires (Hartley & MacLean, 2006;Finlay & Lyons, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…This procedure has been shown to successfully elicit coping responses among adults with mild ID (Hartley & MacLean, 2005;Lunsky, 2003;Wayment & Zetlin, 1989). A sentence stem task has the advantage of avoiding the endorsement of socially desirable responses and other response biases associated with yes-no, either-or and Likert scale questionnaires (Hartley & MacLean, 2006;Finlay & Lyons, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…The ECBS took approximately 5 min for parents to finish, and parents reported that the measure was easy to complete due to its clarity and simplicity. Importantly, the ECBS is simple enough for parents from low-income populations to complete independently, potentially reducing professional time and expenses while increasing response rates (Hartley & MacLean, 2006). Parents of children at risk for behavior problems are more likely than is the general population to have risk factors associated with reading difficulties (Kirsch et al, 2002), and the low reading difficulty of the ECBS should improve the accuracy of the measure for this population.…”
Section: Discussionmentioning
confidence: 97%
“…Questionnaires based on Likert scales are often used in psychometrics, social studies and panels, in marketing research [18,19], or in perceptual-cognitive performance research [20]. The order of presentation of video clips was counterbalanced and randomly determined, during 1 To have full access to the clips please send an email to fcasanova@fade.up.pt and/or jgargant@fade.up.pt Fig.…”
Section: Methodsmentioning
confidence: 99%